Exploring native speaker and non-native speaker accents: The English as a Lingua Franca perspective - Karpal Singh, Paramjit Kaur; Raman, Arumugam (Elsevier Ltd., 2014)
The relevance of the ideology of the native–speaker (NS) as a model and target in English language teaching (ELT) has over the recent years been increasingly questioned with the emergence of English as a Lingua Franca (ELF).Accents that do not conform to NS standards are termed as ‘foreign’ and are usually considered to be something to get rid of by training.This study examines how non-native speakers (NNS) of English view NNS accents in relation to NS accents.The findings show that the respondents consistently ranked NS accents higher than NNS in terms of correctness, acceptability, pleasantness and familiarity.